2011
DOI: 10.1097/ico.0b013e31820156a9
|View full text |Cite
|
Sign up to set email alerts
|

Peters Anomaly: Review of the Literature

Abstract: The clinical features, epidemiology, genetics, complications, and treatments of Peters anomaly are presented. Cornea specialists who care for pediatric patients should be aware of the common and uncommon associations with Peters anomaly. Although bilateral Peters anomaly is much more commonly associated with systemic malformations, we believe that all patients with Peters anomaly should be screened for systemic malformations by both pediatricians and geneticists and undergo chromosomal analysis and molecular g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
110
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(115 citation statements)
references
References 27 publications
0
110
2
3
Order By: Relevance
“…A recently published review of literature reported unilateral disease in 36.8% of 58 cases with Peters anomaly. [10] The rate of unilateral disease, however, was observed in 71.4% of seven patients in this study, but this difference may be attributed to the relatively smaller sample size. Comparably, half of the phakomatoses patients had unilateral disease in this study and this is consistent with published literature which also demonstrate a relatively more even distribution of laterality.…”
Section: Discussioncontrasting
confidence: 58%
“…A recently published review of literature reported unilateral disease in 36.8% of 58 cases with Peters anomaly. [10] The rate of unilateral disease, however, was observed in 71.4% of seven patients in this study, but this difference may be attributed to the relatively smaller sample size. Comparably, half of the phakomatoses patients had unilateral disease in this study and this is consistent with published literature which also demonstrate a relatively more even distribution of laterality.…”
Section: Discussioncontrasting
confidence: 58%
“…[10][11][12][13] Although success rates as high as 83% have been reported 9 in type 1 Peters anomaly, the management of patients with type 2 Peters anomaly remains a challenge because of the high risk of graft failure. 21,22 Both our patients had type 2 Peters anomaly with a more prominent posterior corneal haze and needed other interventions, such as lensectomy, which have been associated with poor prognosis for PKP in some studies. 12,23 With the advantages of PLK over PKP in mind, we decided to perform DSAEK in our cases for a number of reasons.…”
Section: Discussionmentioning
confidence: 95%
“…We selected IVB as the first treatment because it could be performed even in an eye with a corneal opacity. Penetrating keratoplasty was not considered before the treatment for ROP because we knew the results are not favorable in patients with Peters anomaly type II [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Peters anomaly is characterized by congenital corneal opacities, defects of the Descemet's membrane, shallow anterior chambers, cataracts, and glaucoma [1, 2]. The corneal opacities in patients with Peters anomaly make the diagnosis and treatment of retinal disorders such as retinopathy of prematurity (ROP) difficult.…”
Section: Introductionmentioning
confidence: 99%